A study on infant and young child feeding practices among mothers attending an urban health center in East Delhi - Amir Maroof Khan; Priscilla Kayina; Paras Agrawal; Anita Gupta; Anjur Tupil Kannan (Wolters Kluwer Medknow Publications, 2012)
A cross sectional study was conducted to study the diet pattern of children less than 2 years with regard to certain infant and young child feeding (IYCF) indicators. A total of 374 children less than 24 months of age coming to the immunization clinic were studied using a standard pretested and prevalidated questionnaire. Exclusive breastfeeding was followed by 57.1% of children under 6 months of age. Minimum dietary diversity, minimum meal frequency, and minimum acceptable diet were seen adequate in 32.6%, 48.6%, and 19.7% of children between 6 months and 2 years of age, respectively.